2010
DOI: 10.2478/v10009-010-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the plankton assemblages of Lough Derg (Ireland) during a winter-spring season

Abstract: During a winter-spring season, physicochemical variables and plankton dynamics were studied in Lough Derg (Ireland). Samples were collected monthly from three water layers (surface, middle and bottom) at a deep central sampling point on the lake. As expected, phytoand zooplankton densities and chlorophyll a concentrations were low during the study period, probably reflecting low temperatures and wind-driven turbulence typical of the winter-spring period. Diatoms and rotifers were the most abundant phyto-and zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…For example, it is clear that increased light levels would probably increase the predatory efficacy of G. aculeatus , towards both mysids and cladocerans (Townsend & Risebrow ), but the low light levels used in this study reflect the fact that these intermediate and basal prey primarily encounter limnetic G. aculeatus in inshore surface waters during the night (Southern & Gardiner ). In addition, the basal prey concentrations used in our experimental trials fall well within natural abundances found in the field, typically between 1 and 100 individuals L −1 (Southern & Gardiner ; Pociecha, Higgins & McCarthy ). Therefore, we contend that the results presented here should not simply be viewed as an artefact of coercing mixtures of species that lack real‐word relevance.…”
Section: Discussionsupporting
confidence: 71%
“…For example, it is clear that increased light levels would probably increase the predatory efficacy of G. aculeatus , towards both mysids and cladocerans (Townsend & Risebrow ), but the low light levels used in this study reflect the fact that these intermediate and basal prey primarily encounter limnetic G. aculeatus in inshore surface waters during the night (Southern & Gardiner ). In addition, the basal prey concentrations used in our experimental trials fall well within natural abundances found in the field, typically between 1 and 100 individuals L −1 (Southern & Gardiner ; Pociecha, Higgins & McCarthy ). Therefore, we contend that the results presented here should not simply be viewed as an artefact of coercing mixtures of species that lack real‐word relevance.…”
Section: Discussionsupporting
confidence: 71%
“…For the identification and counting of zooplankton species, five replicate sub-samples were analysed microscopically (×100 or ×200) in a chamber of 0.5 ml of volume. Taxonomic analyses of zooplankton (rotifer, copepod and cladoceran taxa) were conducted using keys according to Pociecha et al ( 2010 ). Quantitative samples were prepared by filtering 30 L of water and reducing the sample volume to 50 mL.…”
Section: Methodsmentioning
confidence: 99%
“…We focus in this study on the monogonont rotifer species S. pectinata (Ehrenberg, ), which represents one of the commonest truly planktonic rotifers inhabiting freshwater systems. Due to its comparatively large size for a rotifer (240–550 μm), the species is quite well catalogued (Nogrady & Segers, ), with occurrences documented worldwide, including all of Europe (Arnemo et al ., ; Koste & Voigt, ; Smirnov, ; Marcé et al ., ; Wolska & Piasecki, ; Pociecha, Higgins & Mccarthy, ) as well as parts of Asia, Australia, North and South America and the Arctic (Stemberger, ; Hawkins, ; Chengalath & Koste, ; Sanoamuang, ; Frutos, Poi De Neiff & Neiff, ). Nevertheless, a recent molecular phylogeographic study of populations in the South Tyrol region of Italy argued in favour of cryptic speciation in this species (Obertegger et al ., ).…”
Section: Introductionmentioning
confidence: 99%